Managing Medical Emergencies in Hungarian Pharmacies - Peter P. Felkai; Zsolt Iván (MDPI AG, 2019)
To amass a body of knowledge for managing emergency situations in pharmacies, we surveyed the occurrence and nature of medical problems in Hungarian pharmacies. The occurrence of real or suspected emergencies in pharmacies was markedly different and varied from 1−52 per year, with five cases per year on average. The most frequent problems were bleeding (69%) and dizziness (55%), but other more serious problems (allergic reaction (32%), collapse (23%), and chest pain (25%)) also occurred. Sometimes more than one symptom was reported by a patient. People appear to consider pharmacies to be an appropriate site for receiving first aid for minor ailments, including common medical problems (e.g., fever (12%)). Unfortunately, the range of interventions was very limited because of local legal regulations and the lack of appropriate guidelines for emergencies in pharmacies. The most frequent interventions were wound treatment, control of bleeding (78%), alleviation of anxiety (68%), and providing patients with a glass of water (55%). Very often, more than one intervention was reported for the same case. Whereas 76.3% of pharmacists provided interventions only for adults, 21% of pharmacists provided interventions for all types of patients (adults, co-workers in pharmacies, and children). Pharmacists appeared to be reluctant to treat children, owing to the special issues related to pediatrics. This poor range of intervention should encourage responsible officials to develop guidelines for pharmacists to ensure pharmacists’ familiarity with the appropriate interventions in emergency situations. Such knowledge could also provide a good basis for preparing pharmacists to perform vaccinations in the future. The pharmacists had a positive attitude toward providing first aid, and 88% of respondents requested more postgraduate education on medical first aid issues.